Horrific "Cults" and Comic Religion Manga after Aum - Thomas, Jolyon Baraka 1978- (2012)
After the 1995 Aum Shinrikyō 才ウム真理教 sarin gas attacks, influential commentators suggested that enthralling apocalyptic narratives characteristic of manga (illustrated serial novels) made Aum members prone to extremism and violence. This article inverts this interpretation, showing that popular manga published after 1995 have exhibited—and reflected—morbid fascination with the sensational fodder provided by the Aum incident itself. Early manga responses advanced variations on a horrific "evil cult" trope in which marginal religions modeled on Aum were graphically depicted as hotbeds of sexual depravity, fraud, and violence. Over time, equally chilling—if less sensational—psychological thrillers appeared that interrogated the aspects of human nature that allow for "cult-like" behavior. Finally, one very recent manga has sublimated the formerly popular "evil cult" trope by divorcing "religion" from "cults" and rehabilitating the former through mildly irreverent comedy.
Keywords: Anime; Buddhism; Cults; Evil; Killing; Manga; Narratives; Protagonists; Religious Studies; Religious terrorism